Gender Differences in Enterprise Performance During the COVID-19 Crisis: Do Public Policy Responses Matter?. (September 2022) - Birhanu, Addis G.; Getachew, Yamlaksira S.; Lashitew, Addisu A.
The COVID-19 crisis has introduced unique tradeoffs between health and economic risk, leading to a "life vs. livelihoods conundrum." This study contributes to research on adversity and entrepreneurship by examining the implications of the pandemic for gender differences in enterprise performance. We further consider how public policy responses in the domains of public health and economic support moderate the potential gendered effects of the pandemic. Data analysis of more than 20, 000 enterprises across 38 countries shows that women-owned enterprises were more adversely affected by the pandemic, and that stronger public health policy responses helped reduce the observed gap in performance.